PENGARUH MEDIA GAMBAR DIAM TERHADAP KEMAMPUAN BERBICARA ANAK USIA 5-6 TAHUN DI PAUD KEMUNING KECAMATAN TENAYAN RAYA PEKANBARU - Gusmalinda '; Daviq Chairilsyah; Febrialismanto ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims to determine the effect of a still image media against speaking skills of children aged 5-6 years in early childhood Kemuning Subdistrict Tenayan Raya Pekanbaru. This study was an experimental study design using one group design with pretest and posttest through observation sheet against the child's ability to speak. The sample used in this study of 14 people. The data collection techniques were used that observation. Data were analyzed using t-test using SPSS17.0 program. The study hypothesis is that there is a significant influence on children's ability to speak after applying the still image media. To find out the hypothesis is accepted or rejected based on the data SPSS 17.0 viewable t = 13 745 is greater than table = 1.771 (13 745> 1.771). Hasilpenelitian also see a still image media influence on the ability to speak of children aged 5-6 years. It can be seen from the value of the correlation coefficient (r) of 0.91 with determinant coefficient (r²) = 0.91 x 0.91 = 0.8281 means a still image media influence on the ability to speak is at 82.81% which is the category of very powerful.Keywords: Speech, Media Still Image